2001
DOI: 10.1002/1096-8628(20010122)98:3<216::aid-ajmg1091>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Variegated aneuploidy related to premature centromere division (PCD) is expressed in vivo and is a cancer-prone disease

Abstract: We present three patients with variegated aneuploidy and premature centromere division (PCD), a rare chromosomal abnormality in humans. Comparison of these three and eight other patients with variegated aneuploidy related to PCD demonstrates a phenotype comprising most frequently microcephaly, CNS anomalies (with cerebellar affection and migration defects), mental retardation, pre-and postnatal growth retardation, flat and broad nasal bridge, apparently low-set ears, eye and skin abnormalities, and ambiguous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 31 publications
(59 reference statements)
3
49
0
Order By: Relevance
“…PCS syndrome is a rare autosomal recessive disorder with a high risk of malignancy, including Wilms tumor (Kawame et al, 1999;Kajii et al, 2001;Plaja et al, 2001;Jacquemont et al, 2002). We examined centrosome status in Wilms tumor tissue derived from a PCS syndrome patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCS syndrome is a rare autosomal recessive disorder with a high risk of malignancy, including Wilms tumor (Kawame et al, 1999;Kajii et al, 2001;Plaja et al, 2001;Jacquemont et al, 2002). We examined centrosome status in Wilms tumor tissue derived from a PCS syndrome patient.…”
Section: Discussionmentioning
confidence: 99%
“…PCS syndrome is a rare autosomal recessive disorder characterized by premature separation of sister chromatids of all chromosomes in more than 50% of mitotic lymphocytes and a variety of mosaic aneuploidies, especially trisomies and monosomies (Kajii et al, 1998). Infants with PCS syndrome show growth retardation, severe microcephaly and a high risk of malignancy, such as Wilms tumor and rhabdomyosarcoma (Kawame et al, 1999;Kajii et al, 2001;Plaja et al, 2001;Jacquemont et al, 2002). We previously reported that the cultured skin fibroblasts from two unrelated infants with PCS syndrome showed defects in the spindle assembly checkpoint (Matsuura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It involves not only the centromere but also the entire sister chromatids of almost all mitotic chromosomes in a given metaphase [Kajii and Ikeuchi, 2004]. PSCS has been described in a number of conditions including Roberts syndrome [German, 1979], Fanconi Anemia, Ataxia Teleangiectasia [Mehes and Buhler, 1995], Alzheimer disease [Moorhead and Heyman, 1983;Spremo-Potparevic et al, 2004], Tuberous Sclerosis [Scappaticci et al, 1988], and Variegated Aneuploidy [Kajii et al, 1998;Plaja et al, 2001Plaja et al, , 2003. Recently, mutations in the BUB1B gene were found to be a cause of multiple variegated aneuploidy [Hanks et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether all cases represent the same condition, as some clinical and cytogenetic differences exist among them. For example, mitoses of some of the individuals have a higher frequency of separated centromeres and splayed chromatids in the presence of colcemid, a cytogenetic phenomenon referred to as premature centromere division 8 . The two most common clinical abnormalities of individuals with MVA are microcephaly and intrauterine growth retardation.…”
Section: Mva Syndromementioning
confidence: 99%